Aerosol-cloud-precipitation interactions - Gryspeerdt, E (2013)
Aerosols are thought to have a large effect on the climate, especially through their interactions with clouds. The magnitude and in some cases the sign of aerosol effects on cloud and precipitation are highly uncertain. Part of the uncertainty comes from the multiple competing effects that aerosols have been proposed to have on cloud properties. In addition, covariation of clouds and aerosol properties with changing meteorological conditions has the ability to generate spurious correlations between cloud and aerosol properties. This work presents a new way to investigate aerosol-cloud-precipitation interactions while accounting for the influence of meteorology on cloud and aerosol. The clouds are separated into cloud regimes, which have similar retrieved cloud properties, to investigate the regime dependence of aerosol-cloud-precipitation interactions. The strong aerosol optical depth (AOD)- cloud fraction (CF) correlation is shown to have the ability to generate spurious correlations. The AOD-CF correlation is accounted for by investigating the frequency of transitions between cloud regimes in different aerosol environments. This time-dependent analysis is also extended to investigate the development of precipitation from each of the regimes as a function of their aerosol environment. A modification of the regime transition frequencies consistent with an increase in stratocumulus persistence over ocean is found with increasing AI (aerosol index). Increases in transitions into the deep convective regime and in the precipitation rate consistent with an aerosol invigoration effect are also found over land. Comparisons to model output suggest that a large fraction of the observed effect on the stratocumulus persistence may be due to aerosol indirect effects. The model is not able to reproduce the observed effects on convective cloud, most likely due to the lack of parametrised effects of aerosol on convection. The magnitude of these effects is considerably smaller than correlations found by previous studies, emphasising the importance of meteorological covariation on observed aerosol-cloud-precipitation interactions.